Planet earth and the universe - Brewer, Duncan, 1938- (Brewer, Duncan, 1938-. Planet guides., 1992)
Examines the physical characteristics and conditions of the Earth, describing its position in relation to the sun and other planets and surveying humanity's attempts to penetrate its mysteries.